Momentum-space non-hydrogenic wavefunction of quantum defect theory - Chaudhuri, P.; Talukdar, B.; Adhikari, S. K. (Iop Publishing Ltd, 1999)
We derive a closed-form analytic expression in momentum space for the asymptotic non-hydrogenic wavefunction of the quantum defect theory (QDT) due to Seaton and compare it with a widely used QDT-approximate wavefunction for the Rydberg states Li-3(2s), Mg-24(6s) and Rb-37(5s).